Development of a technique to control and ensure the predefined porosity of a grain layer in the pneumo-separating channel at a grain heap cleaner - Volkhonov, Michael; Bushuev, Ivan; Volkhonov, Roman; Pashin, Evgeny (Eastern-European Journal of Enterprise Technologies, 2019)
To operatively control the state of a layer of the separated grain heap, while cleaning it from impurities in a pneumo-separating channel, it has been suggested to use ultrasonic waves with a frequency of 40 kHz. We have established the relationship between supplying air and a material on the difference from the average values for the lengths of ultrasonic waves paths, acquired from ultrasonic range finders, which are installed at the beginning, in the middle, and at the end of a pneumo-separating channel. Based on this pattern, we have designed a means to control and ensure the predefined porosity of the grain layer in a pneumo-separating channel of the grain layer cleaner. The technique is based on the principle of continuous calculation of the difference between the average values for the lengths of ultrasonic waves paths, acquired from range finders, located inside a pneumo-separating channel. The obtained values are transmitted to the control unit in order to process them by comparing the obtained values with the specified ones. Should a deviation in the obtained values from those specified occur, one has to adjust the supply of a material and/or air to the pneumo-separating channel. The developed means of operative control over the state of a separated layer makes it possible, during cleaning, to maintain grains in a suspended condition at the assigned level of fluidization. This ensures the best conditions for the removal of waste impurities throughout the entire volume of a grain layer, the high quality of grain cleaning at high efficiency of the cleaner.